Analisis Kebutuhan Kapal Tongkang dan Tugboat pada Distribusi Crude Palm Oil (CPO) - Shabrina Rifa; Juang Akbardin; Dwi Novi Wulansari (Pusat riset dan Inovasi Nasional, 2026)
This study aims to analyze the need for barges and tugboats in distributing Crude Palm Oil (CPO) in the West Papua region. The analysis is conducted based on three main aspects: the balance of supply and demand, ship operational costs, and shipping time, to determine the most efficient mode of sea transportation. The research method used is a quantitative approach by processing CPO distribution data owned by PT Kurhanz Trans in 2024. The results show that the combination of a 240-foot barge with a 5,000 HP tugboat is the most optimal alternative. This combination is able to balance cargo capacity, operational cost efficiency, and shipping time. The total operating cost of a 240-foot barge is recorded as lower than a 230-foot barge, with the same shipping time of 70 hours for a distance of 140 nautical miles. Thus, the 240-foot barge can be recommended as the best alternative to support the smooth distribution of CPO in the West Papua region efficiently and economically.